Sustainable transport futures : pathways and political economies - Hickman, R; Banister, D (Universities' Transport Study Group, 2012)
Over the last fifty years there has been much interest in cities – in their planning, design, degradation and regeneration – and in the last ten years, in particular, much discussion around sustainability, reducing greenhouse gas (GHG) and carbon dioxide (CO2) emissions. Within this, there are aspirations towards sustainable travel. Progress however appears intractably difficult to make in the transport sector as the private car, largely fuelled by petrol or diesel, remains the mainstream mode of use and choice. In almost all cities we are experiencing increasing emissions in transport, the city fabric is often adversely impacted by planning for the private car, and many people complain of the daily grind of the commute as the worst part of their daily lives. Our travel behaviours are in crisis. This paper considers the different baselines, projections and opportunities for five very different contexts: from London and Oxfordshire (UK), Delhi (India), Jinan (China) and Auckland (New Zealand). The likely possibilities for reducing transport CO2 emissions are examined relative to the aspirations of the IPCC (2007) and Stern (2007, 2009). The IPCC’s central scenario (A1F1), assuming high economic growth and increased globalisation, estimates resultant world temperature increases of 4°C-6.4°C and expected sea level rises of up to 59cm, with hugely variable impacts globally. A central issue, therefore, is in the gap between the current business as usual (BAU) projections and the strategic policy ambitions to reduce the likely impacts of climate change. Scenarios are developed, assuming an equitable 0.5 tCO2 per capita in transport CO2 emissions, for each case study by 2050. The political deliverability of low carbon transport futures, however, remain a major obstacle to progress (Hood, 1986; Freund and Martin, 1993; Dunn and Perl, 2010). The growing body of scenario analysis and modelling of impacts by policy tool or package of tools is useful, but in the end redundant, if political deliverability is not possible. The paper therefore concludes in examining the scenarios insofar as the degree of public authority (legitimate coercion) required in implementation. Potential future transport behaviours are thus given greater credibility in terms of resilience.